Procurement of Simple Street Lighting Based on Solar Panels in the Limo Area to Enhance Energy Resilience - Teuku Rifath Abizar (Indonesian Journal of Electrical Engineering and Electronics, 2024)
This research aims to develop a street lighting solution in the Limo area using solar panel-based lighting technology. Using thin-film solar panels with an efficiency of 7-13% and a maximum power of 200WP, solar energy is converted into electricity and stored in batteries. Simulations show that the solar panels can produce 1 KWh of energy, allowing storage of approximately 312.3Ah in the batteries. LED lights, which consume 22.94 Ah, can provide illumination for 13.613 hours. Motion sensors activate the lights only when movement is detected, optimizing energy use. The evaluation indicates that this research contributes positively to increasing public understanding of Renewable Energy (EBT), encourages the adoption of solar technology, and raises awareness about the importance of energy and water resilience. The findings highlight the potential for sustainable lighting with renewable energy and its social impact on the community.